FROM CUSTOMARY GOVERNANCE TO BIODIVERSITY CONSERVATION: LEGAL PROSPECTS FOR COMMUNITY-BASED COASTAL RESOURCE MANAGEMENT AS OECMs IN INDONESIA - Sri Wahyu Ananingsih; Nur Adhim; Agung Muhammad Siradj (Masalah-Masalah Hukum, 2026)
This study examines the legal challenges and necessary measures for recognising community-based coastal resource management practices in Indonesia as Other Effective Area-Based Conservation Measures (OECMs). As the Kunming-Montreal Global Biodiversity Framework requires the conservation of at least 30 percent of terrestrial, inland water, coastal, and marine areas by 2030, OECMs have become an important instrument for expanding conservation beyond formal protected areas. Indonesia has significant potential to implement OECMs because many coastal and customary communities have long maintained local resource management systems, such as sasi, panglima laot, awig-awig, egek, parimpari, papadak, and other customary practices. These systems reflect community stewardship, ecological sustainability, local wisdom, and social legitimacy. However, their integration into the formal OECM framework remains legally and institutionally complex. Using a non-doctrinal research design with a socio-legal approach, this study draws on in-depth interviews with customary leaders from Wakatobi Island, the Kei Islands, and the Jambi Malay Customary Institution, supported by participant observation and secondary legal and policy analysis. The findings show that the recognition of community-based coastal resource management as OECMs is constrained by the absence of specific OECM regulations, fragmented natural resource governance, overlapping sectoral authority, reduced district and municipal roles in marine management, limited legal recognition of customary law communities, and weak community capacity in documentation, monitoring, and reporting. The study also finds that government policy risks treating OECMs as an administrative tool for meeting global conservation targets rather than as a substantive framework for biodiversity protection and community empowerment. This study argues that effective OECM implementation requires a comprehensive legal framework, harmonised conservation and natural resource regulations, accelerated recognition of customary law communities, meaningful participation based on Free, Prior and Informed Consent, and capacity-building support for local communities. Recognising community-based coastal management practices as OECMs can strengthen biodiversity conservation, provide legal certainty and protection, and affirm communities as legitimate rights holders in sustainable coastal governance.